Influence of buccal bony crest width on marginal dimensions of peri-implant hard and soft tissues after implant installation. An experimental study in dogs - Baffone, Gabriele M.; Botticelli, Daniele [UNESP]; Pereira, Flavia Priscila [UNESP]; Favero, Giacomo; Schweikert, Michael; Lang, Niklaus P. (Wiley, 2013)
Aim: To evaluate the influence of the width of the buccal bony wall on hard and soft tissue dimensions following implant installation. Material and methods: Mandibular premolars and first molars of six Labrador dogs were extracted bilaterally. After 3 months of healing, two recipient sites, one on each side of the mandible, were prepared in such a way as to obtain a buccal bony ridge width of about 2 mm in the right (control) and 1 mm in the left sides (test), respectively. Implants were installed with the coronal margin flush with the buccal alveolar bony crest. Abutments were placed and the flaps were sutured to allow a non-submerged healing. After 3 months, the animals were euthanized and ground sections obtained. Results: All implants were completely osseointegrated. In respect to the coronal rough margin of the implant, the most coronal bone-to-implant contact was apically located 1.04 ± 0.91 and 0.94 ± 0.87 mm at the test and control sites, respectively, whereas the top of the bony crest was located 0.30 ± 0.40 mm at the test and 0.57 ± 0.49 mm at the control sites. No statistically significant differences were found. A larger horizontal bone resorption, however, evaluated 1 mm apically to the rough margin, was found at the control (1.1 ± 0.7 mm) compared to the test (0.3 ± 0.3 mm) sites, the difference being statistically significant. A thin peri-implant mucosa (2.4-2.6 mm) was found at implant installation while, after 3 months of healing, a biological width of 3.90-4.40 mm was observed with no statistically significant differences between control and test sites. Conclusions: A width of the buccal bony wall of 1or 2 mm at implant sites yielded similar results after 3 months of healing in relation of hard tissue and soft tissues dimensions after implant installation. © 2012 John Wiley & Sons A/S.
Keywords: Animal study; Bone healing; Bone levels; Histometry; Implant dentistry; Oral implants; Soft tissue dimensions